Aging and Aging-Related Senescence in Liver - Ganguly, Souradipta; Sakane, Sadatsugu; Hokutan, Kanani; Zhang, Vivian; Miciano, Charlene; Wang, Allen; Brenner, David A.; Kisseleva, Tatiana (Seminars in Liver Disease, 2025)
Aging is characterized by the progressive deterioration of cell and tissue functions. The liver, which regulates metabolic homeostasis, detoxification, and immune responses, undergoes structural and functional changes with age. These include increasing genomic instability, telomere attrition, epigenetic alterations, loss of proteostasis, deregulated nutrient-sensing and intracellular communication, mitochondrial dysfunction, cell senescence, stem cell exhaustion, chronic inflammation, disabled macroautophagy, and dysbiosis. These alterations contribute to hepatocyte dysfunction, impaired regenerative responses, and fibrosis risk, which all exacerbate existing liver diseases. Senescence involves irreversible cell cycle arrest resulting in an inflammatory, senescence-associated secretory cell phenotype. Senescent hepatocytes, liver sinusoidal endothelial cells, hepatic stellate cells, and Kupffer cells accumulate in the aged liver, creating an inflammatory and fibrotic microenvironment that promotes tumorigenesis. As the burden of aging-related liver disease increases, therapeutic strategies targeting hepatic senescence have gained attention. We review these, along with the mechanisms and pathogenic effects of liver aging.
Keywords: SASP; LSEC; HSC; cancer; carcinogenesis